Productivity Improvement For Peddle Driven Sewing Machine with RSM Technique - Swapna Ghatole, Yashpal, Mahesh Bundele, J. P. Modak (International Journal of Modern Agriculture, 2021)
The ergonomic evaluation of sewing machine operation practices are traditionally studied by several investigators in the past. The study highlights various occupational health hazards of this operation. This study published through literature describes occupational health hazard in terms of various causes of this activity .Stand alone pedal driven sewing operation, consists of a operator, stand alone pedal driven sewing machine, workstation, environmental conditions which is called as a man machine system. Data of 30 Indian workstations is collected. 40 causes / input / independent variables and effects/ output /dependant variables are used for study and are converted into five independent dimensionless terms known as pi terms as pi1,pi2, pi3, pi4,pi5. And the effects or dependant term is stated as Z3 for productivity. The mathematical co-relationships are established on the independent and dependant parameters. Response surface model concept is used for the study to a show perfect connection and nearness with the outcomes from RSM technique which can be used for future design of workstation for sewing machine.